PENILAIAN KINERJA PT PERKEBUNAN NUSANTARA VII (PERSERO) UNIT USAHA BETU DENGAN PENDEKATAN BALANCED SCORECARD - Unggu Prayogi; Yulia Saftiana; Aryanto Aryanto (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
Performance evaluation is an essential factor for a company. Performance evaluation used in this research is Balanced Scorecard. The goal of this research is to identify the performance of the company through four different perspectives: financial perspective, customer perspective, internal business processing perspective and growth and development perspective. This research is a case study using descriptive analisis technique. Performance evaluation in this research is the data from PT Perkebunan Nusantara VII (Persero) Unit Usaha Betu in the year of 2011 and 2012. Based on this research it is concluded that the overall performance evaluation for PT Perkebunan Nusantara VII (Persero) Unit Usaha Betu is good. This is based from the scoring using the Balanced Scorecard approach inducted from financial perspective, customer perspective, internal business processing perspective and growth and development perspective. To increase what the company performance had already achieved, the writer suggestion for the company is to pay more attention to the internal business processing perspective. Especially the ones concerning raw material quality supervision, production process and product quality, in order for the product to meet the standard set by the company that eventually will impact the company’s performance in terms of financial perspective, customer perspective and growth and development perspective.